ヒト血清アルブミン-チオレドキシン融合蛋白質は都市大気粉塵による急性肺傷害を予防する - 田中, 健一郎; 池田, 真由美; 異島, 優; 川原, 正博; 久保田, 真帆; 下田, 実可子 (日本薬理学会年会要旨集, 2021)
Air pollution is a major health hazard that causes an estimated 8.8 million deaths per year worldwide, which is greater than the number of deaths due to smoking. Air pollutants, such as PM2.5, are known to induce respiratory and cardiovascular diseases by inducing oxidative stress. Thioredoxin (Trx) is a 12-kDa endogenous protein that exerts antioxidant activity by promoting dithiol disulfide exchange reactions. We previously synthesized human serum albumin-fused thioredoxin (HSA-Trx), which has a longer half-life in plasma compared with Trx, and demonstrated its efficacy against various diseases including respiratory diseases. Here, we examined the effect of HSA-Trx on urban aerosol-induced lung injury in mice. Urban aerosols induced lung injury and inflammatory responses in ICR mice, but intravenous administration of HSA-Trx markedly inhibited these responses. We next analyzed reactive oxygen species (ROS) production in murine lungs using an in vivo imaging system. The results show that intratracheal administration of urban aerosols induced ROS production that was inhibited by intravenously administered HSA-Trx. Finally, we found that HSA-Trx inhibited the urban aerosol-induced increase in levels of neutrophilic extracellular trap (NET) indicators in bronchoalveolar lavage fluid. Together, these findings suggest that HSA-Trx prevents urban aerosol-induced acute lung injury by suppressing ROS production and neutrophilic inflammation. Thus, HSA-Trx may be a potential candidate drug for preventing the onset or exacerbation of lung injury caused by air pollutants.